Characterization of genetic fundamentals for piglet mortality at birth in Yorkshire, Landrace, and Duroc sows. (13th December 2021) - An, M.; Zhou, G.; Li, Y.; Xiang, T.; Ma, Y.; Liu, X.; Li, X.; Zhao, S.; Zhu, M.
Summary: Piglet mortality is an economically important complex trait that impacts sow prolificacy. Genetic analyses for piglet mortality at weaning have been reported in dozens of studies, but not for piglet mortality at birth. In this study, we used multi‐breed data sets from Yorkshire, Landrace, and Duroc sows to characterize the genetic fundamentals of piglet mortality at birth. The heritabilities from parity I to III were estimated to be 0.0630, 0.1031, and 0.1140 respectively. By using a combined strategy, a total of 21 SNPs were detected in three parities, of which six were observed in parity I, five in parity II and 10 in parity III. Genome annotation revealed that these SNPs were harbored within or close to 19 candidate genes. The candidate genes were found to associate with the reproductive system and embryonic development in the tissue expression database, which are reasonably related to piglet mortality. These findings are expected to provide much information for understanding the genetic and genomic fundamentals of farrowing mortality.